ANALISIS TINGKAT KEPUASAN PASIEN PENERIMA PROGRAM KESEHATAN GRATIS DI RUANG PERAWATANKELAS TIGA RUMAH SAKIT UMUM DAERAH (RSUD) ANDI SULTHAN DG. RAJA KABUPATEN BULUKUMBA - Sumarlin Sumarlin (Jurnal Kesehatan dan Sains, 2017)
The objective of this Research is to know (1) Reliability (mainstay), (2) Responsiveness (caring or comments), (3) Assurance (certainty guarantee), (4) Emphaty (care) and (5) Tangibles (real form) give effect of patient satisfaction Receiverof Free Health Program whichtaking care of to lodge in classroom of the third class Regional General Hospital (RSUD) Andi Sulthan of Dg. Raja of Bulukumba Regency. This research was conducted at the Regional General Hospital (RSUD) Andi Sulthan of Dg. Raja of Bulukumba Regency on March to April 2015. Research type which using survey (research explanatory) with 97 patients which as samples in taking care of to lodge grade three respondents. Method of research was descriptive analysis with technique of proportionate sampling random used program of SPSS 15,0. The result showed that of five component of positive and significant impact on the level of patient satisfaction in treatment room of class three hospital Andi Sulthan Dg. Raja of Bulukumba, including (1)Reliability with sign ????= 0.2, (2) tangibles with sign ????= 0.045, (3) assurance with sign ????=0.3, (4) care with sign ????= 000 and (5) responsiveness with sign ????= 0.08. This indicates receipt stating that there is a positive and significant influence between independent variable on dependent variable.